2017
DOI: 10.1016/j.chemosphere.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Remediation efficiency of three treatments on water polluted with endocrine disruptors: Assessment by means of in vitro techniques

Abstract: Chemical substances with potential to disrupt endocrine systems have been detected in aquatic environments worldwide, making necessary the investigation about water treatments able to inhibit such potential. The present work aimed to assess the efficiency for removing endocrine disruptors (with estrogenic and androgenic activity) of three simple and inexpensive substrates that could be potentially used in sectors or regions with limited resources: powdered activated carbon (PAC), powdered natural zeolite (ZEO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Cluster 3 (blue), "NZ water purification", is formed by 10 nodes with 379 co-occurrences. Various topics on water purification are dealt with, presenting methods such as desalination and de-oiling of water with natural zeolite membranes [34], treatments for nitrate removal [105], treatments are evaluated in waters contaminated with endocrine disruptors [106] and even the purification of groundwater [107], with keywords "purification", "water quality", and "clinoptilolite".…”
Section: Author's Keyword Co-occurrence Networkmentioning
confidence: 99%
“…Cluster 3 (blue), "NZ water purification", is formed by 10 nodes with 379 co-occurrences. Various topics on water purification are dealt with, presenting methods such as desalination and de-oiling of water with natural zeolite membranes [34], treatments for nitrate removal [105], treatments are evaluated in waters contaminated with endocrine disruptors [106] and even the purification of groundwater [107], with keywords "purification", "water quality", and "clinoptilolite".…”
Section: Author's Keyword Co-occurrence Networkmentioning
confidence: 99%
“…The adsorption process with activated carbon (AC) is considered by many authors to be one of the most promising treatment processes with high EP removal capacity, mainly because (i) it is simple to design and operate; (ii) it has a low investment cost; (iii) it allows reuse and regeneration; and (iv) it does not generate toxic by-products [8,19,[21][22][23][24]. Several studies have also already demonstrated that pure AC is able to effectively remove and lower the toxicity of E2 and EE2 in distilled water, drinking water and WW [25][26][27][28][29][30][31][32][33][34][35]. For example, Gökçe and Arayici [33] obtained a removal rate for E2 of 88% with AC produced from sewage sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitation of water and arable land resources, an urgent need is requested to increase effective use of these resources as well as minimize the agro-ecology damage by using the effective modern technologies like nanotechnology (Manjunatha et al 2016). Several applications of nanotechnologies can be addressed in the developing countries including production, conversion and storage energy (like CNT storage of H; Zhang et al 2014(a or b); Li and Sun 2016;Liu et al 2017), enhancement of the agricultural productivity (like herbicide delivery; Pandey et al 2016;Chhipa and Joshi 2016), water treatment and remediation (like nano-membranes; Toli et al 2016;Polloni-Silva et al 2017), diagnosis and screening of diseases Mignani et al 2017), delivery systems of drugs (like nanocapsules; Nawaz and Wong 2017;, processing, coating, packaging and storage of foods (Carbone et al 2016;Sarkar et al 2016;Chalco-Sandoval et al 2017), remediation of air pollution (like nano-catalysts; Kuppusamy et al 2016), durability of construction (Balapour et al 2017;Fallah and Nematzadeh 2017), monitoring Env. Biodiv.…”
Section: Introductionmentioning
confidence: 99%